Lower life expectancy among people with an HCV notification: a population‐based linkage study. Issue 6 (June 2014) - Alavi, M.; Law, M. G.; Grebely, J.; Thein, H. H.; Walter, S.; Amin, J.; Dore, G. J.
Summary Among people with hepatitis C virus (HCV) infection, liver disease‐related deaths have risen over the last 20 years. Life expectancy has not been estimated in this population. HCV notifications (mandatory notification of anti‐HCV‐positive serology since 1991) reported to the New South Wales Health Department from 1992 to 2006 were linked to cause of death data. Abridged life tables were constructed from age‐specific mortality rates. Life expectancy from ages 18–70 years for non‐drug‐related mortality causes was estimated using competing risk methods and compared to the general population of Australia. The cohort comprised 81 644 individuals with an HCV notification, with median follow‐up of 7.6 years. Median age at notification was 34 years [interquartile range (IQR) 28–42] and 63% were male. Between 1992 and 2006, 4607 deaths occurred. Median age at liver‐ and drug‐related death among males was 51 (IQR 45–66) and 36 (IQR 31–42) years, respectively, and among females was 63 (IQR 49–74) and 36 (IQR 30–41) years, respectively. In each year of follow‐up before 2000, 15–21% of deaths were liver‐ and 30–39% were drug‐related. After 2000, liver‐related deaths increased to 20–26% of deaths in each year and drug‐related deaths decreased to 13–19%. Excluding drug‐related causes of death, life expectancy was lowered by an average of 4.2 (SD ± 1.0) and 5.4 (SD ± 0.7) years for males and females, respectively. Among people with an HCV notification, an increasing proportion of deaths are liver‐related. Following removal of drug‐related mortality, life expectancy in this population remained considerably lower, compared with the general population.